2007
DOI: 10.1007/s10347-006-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Progressive drowning of carbonate platform in the Moravo-Silesian Basin (Czech Republic) before the Frasnian/Famennian event: facies, compositional variations and gamma-ray spectrometry

Abstract: The Moravo-Silesian Basin (MSB; eastern Czech Republic and southern Poland) hosted an extensive shallow-water carbonate platform in the Middle Devonian to Frasnian interval. The platform drowned in a stepwise fashion from the Palmatolepis hassi to the Pa. linguiformis zone. Three types of drowning successions were revealed from conodont biostratigraphy, facies, microfacies and gamma-ray spectrometry data: (A) drowning to periplatform turbidite setting; (B) drowning to (hemi)pelagic seamount setting and (C) dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 53 publications
1
25
0
1
Order By: Relevance
“…These characteristic horizons are composed of material that has evidently been redeposited from the neighbouring shallow-water platform. Usually, the trigger mechanism leading to the deposition of such intercalations is interpreted as being induced by earthquakes or storms (e.g., Szulczewski 1968;Aigner 1985;Bábek et al 2007) but recently Jorry et al (2010) have proposed another explanation. Their analysis of the sedimentary infilling of modern basins (or atoll lagoons) that are adjacent to periodically flooded carbonate platforms has indicated that the export of carbonate material by gravity mass flows can be triggered also by a glacieustatic sea-level rise.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristic horizons are composed of material that has evidently been redeposited from the neighbouring shallow-water platform. Usually, the trigger mechanism leading to the deposition of such intercalations is interpreted as being induced by earthquakes or storms (e.g., Szulczewski 1968;Aigner 1985;Bábek et al 2007) but recently Jorry et al (2010) have proposed another explanation. Their analysis of the sedimentary infilling of modern basins (or atoll lagoons) that are adjacent to periodically flooded carbonate platforms has indicated that the export of carbonate material by gravity mass flows can be triggered also by a glacieustatic sea-level rise.…”
Section: Discussionmentioning
confidence: 99%
“…Dvořák & Friáková 1978;Galle et al 1988;Hladil 1983Hladil , 1988Hladil , 1994Hladil , 2002Hladil et al , 2006aBábek et al 2007) (Fig. 2).…”
Section: Methodology and Data Setsunclassified
“…Various parts of outer carbonate platforms and inner Laurussian carbonate shelf were juxtaposed. The evidence exists that the individual blocks were transposed and former deep-water basins were closed, deformed, and locally obliterated (Racki 1993, Vierek 2007, Hladil 2002, Bábek et al 2007). These sutures were often rejuvenated with younger faults in the Saxonian, NW-SE direction.…”
Section: Geological Settingmentioning
confidence: 99%
“…Bábek et al 2007) and can therefore serve as a reference for other studies in similar facies. In the presented study the analysis proved to be a useful tool for correlation purposes and for identification of depositional systems.…”
Section: Final Remarks and Study Perspectivesmentioning
confidence: 99%